2022
DOI: 10.13037/gr.vol38n113.7017
|View full text |Cite
|
Sign up to set email alerts
|

REGIONALIZAÇÃO DA SAÚDE NO BRASIL: Desigualdades socioeconômicas e na performance em saúde

Abstract: Este artigo visa compreender os padrões das regiões de saúde no Brasil quanto à performance em saúde e às condições socioeconômicas. Para atingi-lo, utilizou-se de 2 análises de clusters das 438 regiões de saúde, composta de indicadores de condicionantes estruturais e dimensões de saúde. A primeira análise de clusters empregou os 3 indicadores que compõem os condicionantes estruturais, e a segunda análise de clusters as 6 dimensões de saúde. Os resultados demonstram que as regiões de saúde com os piores valore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(33 reference statements)
1
1
0
1
Order By: Relevance
“…These regions are home to centers of excellence for treatment of neuromuscular diseases in the public health care system (i.e., the Sarah Kubitschek Hospitals) or major academic centers, where muscle biopsies and genetic tests are available. This is consistent with findings of Paschoalotto et al [ 33 ] and Horovitz [ 34 ] that demonstrated most care centers and services in the area of clinical genetics are concentrated in the most developed regions of the country. We were unable to determine if the database over- or under-represents rural vs. urban regions.…”
Section: Discussionsupporting
confidence: 93%
“…These regions are home to centers of excellence for treatment of neuromuscular diseases in the public health care system (i.e., the Sarah Kubitschek Hospitals) or major academic centers, where muscle biopsies and genetic tests are available. This is consistent with findings of Paschoalotto et al [ 33 ] and Horovitz [ 34 ] that demonstrated most care centers and services in the area of clinical genetics are concentrated in the most developed regions of the country. We were unable to determine if the database over- or under-represents rural vs. urban regions.…”
Section: Discussionsupporting
confidence: 93%
“…Results from the REAL study (2020) of 1115 patients with RA treated at 11 public (SUS) centers across Brazil reported a median age of 56.6 years, 89.5% female, and 58.6% white 29 . Although potential genetic factors may contribute to RA predisposition among whites/Caucasians (proposed in REAL study) 29 , and more than half (52.9%) of patients in our study were from the south and southeast regions in Brazil where there is a high proportion of white/Western European ethnic population, this region benefits from better access to healthcare from a higher concentration of physicians 30 , 31 . The geographic heterogeneity found in our study is in line with previous Brazilian perspectives findings of patients with RA 32 .…”
Section: Discussionmentioning
confidence: 72%
“…Tem atividades que precisamos executar, mas que infelizmente acabamos não fazendo porque o tempo é insuficiente. (6°GL) Embora a integralidade das ações ofertadas na UBSF tenha sido reconhecida como incipiente, as condições de atendimento na UBSF não diferem significativamente da capacidade instalada nas unidades básicas da região Norte 19,20 , reconhecidas na literatura como carentes de boas instalações e marcadas pela fragilidade das ações intersetoriais e de promoção da saúde 14,17,21 .…”
Section: Temporalidades Diversificadasunclassified